Software, Animation and the Moving Image What's in the Box? - Wood, A. (Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2015)
Software, Animation and the Moving Image brings a unique perspective to the study of computer-generated animation by placing interviews undertaken with animators alongside an analysis of the user interface of animation software. Wood develops a novel framework for considering computer-generated images found in visual effects and animations.